Current status of waste management in Botswana: A mini-review. Issue 7 (July 2018) - Mmereki, Daniel
Effective waste management practices are not all about legislative solutions, but a combination of the environmental, social, technical, technically skilled human resources, financial and technological resources, resource recycling, environmental pollution awareness programmes and public participation. As a result of insufficient resources, municipal solid waste (MSW) in transition and developing countries like Botswana remains a challenge, and it is often not yet given highest priority. In Botswana, the environment, public health and other socio-economic aspects are threatened by waste management practices due to inadequate implementation and enforcement mechanisms of waste management policy. This mini-review paper describes the panorama of waste management practices in Botswana and provides information to competent authorities responsible for waste management and to researchers to develop and implement an effective waste management system. Waste management practices in Botswana are affected by: lack of effective implementation of national waste policy, fragmented tasks and overlapping mandates among relevant institutions; lack of clear guidelines on the responsibilities of the generators and public authorities and on the associated economic incentives; and lack of consistent and comprehensive solid waste management policies; lack of intent by decision-makers to prepare national waste management plans and systems, and design and implement an integrated sustainable municipal solid waste management system. Due to these challenges, there are concerns over the growing trend of the illegal dumping of waste, creating mini dumping sites all over the country, and such actions jeopardize the efforts of lobbying investors and tourism business. Recommendations for concerted efforts are made to support decision makers to re-organize a sustainable waste management system, and this paper provides a reference to other emerging economies in the region and the world.